Treatment Preferences for Active Surveillance vs. Active Treatment Among Men with Low-Risk Prostate Cancer - Taylor, Kathryn L. (Cancer Epidemiol Biomarkers Prev, 2016)
BACKGROUND: Due to the concerns about the overtreatment of low-risk prostate cancer (PCa), active surveillance (AS) is now a recommended alternative to the active treatments (AT) of surgery and radiotherapy. However, AS is not widely utilized, partially due to psychological and decision-making factors associated with treatment preferences. METHODS: In a longitudinal cohort study, we conducted pretreatment telephone interviews (N=1,140, 69.3% participation) with newly diagnosed, low-risk PCa patients (PSA≤10, Gleason≤6) from Kaiser Permanente Northern California. We assessed psychological and decision-making variables, and treatment preference [AS, AT, No Preference (NP)]. RESULTS: Men were 61.5 (SD=7.3) years old, 24 days (median) post-diagnosis, and 81.1% white. Treatment preferences were: 39.3% AS, 30.9% AT, and 29.7% NP. Multinomial logistic regression revealed that men preferring AS (vs. AT) were older (OR=1.64, CI 1.07-2.51), more educated (OR=2.05, CI 1.12-3.74), had greater PCa knowledge (OR=1.77, CI 1.43-2.18) and greater awareness of having low-risk cancer (OR=3.97, CI 1.96-8.06), but also were less certain about their treatment preference (OR=0.57, CI 0.41 - 0.8), had greater PCa anxiety (OR=1.22, CI 1.003-1.48), and preferred a shared treatment decision (OR=2.34, CI 1.37-3.99). Similarly, men preferring NP (vs. AT) were less certain about treatment preference, preferred a shared decision, and had greater knowledge. CONCLUSIONS: Although a substantial proportion of men preferred AS, this was associated with anxiety and uncertainty, suggesting that this may be a difficult choice. IMPACT: Increasing the appropriate use of AS for low-risk PCa will require additional reassurance and information, and reaching men almost immediately post-diagnosis while the decision-making is ongoing.